A comparative review on clean hydrogen production from wastewaters. (1st February 2021) - Aydin, Muhammed Iberia; Karaca, Ali Erdogan; Qureshy, Ali M.M.I.; Dincer, Ibrahim
Abstract: This paper provides a unique review of hydrogen production methods with wastewater treatment to depict a clean and sustainable approach. Various methods for hydrogen production from wastewaters are identified and discussed with recent details by discussing the critical challenges, opportunities, and future directions. Five main performance sectors are considered in detail for each hydrogen production method of the recent case studies, including economic, environmental, social, technical, and reliability. Eight hydrogen production methods are reviewed, including anaerobic method, photo fermentation, dark fermentation, electrolysis, electrodialysis, photocatalysis, photoelectrochemical methods, and super water gasification. A comparative assessment of six reviewed methods for hydrogen production, including environmental, economic, energetic, and exergetic impacts, is evaluated. The comparative assessment results indicate that dark fermentation technology is the most economical method, and it is followed by microbial electrolysis and photofermentation. The most environmentally friendly method for the lowest global warming potential (GWP) is the microbial electrolysis method, and it is followed by photocatalysis and photoelectrochemical methods. Furthermore, the highest energy and exergy efficiencies have been recorded for the microbial electrolysis to be 68% and 64.7%, respectively. Highlights: Hydrogen production methods, along with wastewater treatment, are reviewed. A comparative study of the nine hydrogen production methods is performed. The results indicate the dark fermentation method is the most economical method. The microbial electrolysis method is listed as the lowest environmental impact.